Effect Of Pig Manure Incubation As Organic Fertilizer On The Growth Of Lettuce (Lactuca sativa L.) - Yosia Ririn; Diane D Pioh; Ronny Nangoi (Jurnal Agroekoteknologi Terapan, 2022)
Manure is a fertilizer that comes from a mixture of livestock manure, urine, and leftover animal feed. The purpose of the study was to see how the growth of lettuce plants that were given pig manure were incubated. This study used a completely randomized design (CRD) with 9 treatments, namely T0 (control), T2 (0 weeks incubation without soaking), T1 (1 week incubation without soaking), T3 (2 weeks incubation without soaking), T4 (3 weeks incubation without soaking). without soaking), T5 (0 weeks of immersion incubation), T6 (1 week of soaking incubation), T7 (2 weeks of soaking incubation), T8 (3 weeks of soaking incubation), each treatment was repeated 3 times to obtain 27 experimental plants. Parameters observed were plant height, number of leaves, fresh weight, and root volume. Based on the results of the study it can be concluded that the application of organic fertilizer from pig manure which was incubated with immersion and without immersion had no significant difference to plant height, number of leaves, and root volume but significantly different to fresh weight of lettuce plants. Keywords: Organic fertilizer, manure, pig manure, incubation, lettuce plant. Abstrak Pupuk kandang adalah pupuk yang berasal dari campuran kotoran ternak, urine, dan sisa pakan ternak. Tujuan penelitian adalah untuk melihat bagaimana pertumbuhan tanaman selada yang diberi kotoran babi yang diinkubasi. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 9 perlakuan yaitu T0 (kontrol), T2 (inkubasi 0 minggu tanpa perendaman), T1 (inkubasi 1 minggu tanpa perendaman), T3 (inkubasi 2 minggu tanpa perendaman), T4 (3 minggu inkubasi tanpa perendaman). minggu inkubasi tanpa perendaman). tanpa perendaman), T5 (0 minggu inkubasi perendaman), T6 (1 minggu inkubasi perendaman), T7 (2 minggu inkubasi perendaman), T8 (3 minggu inkubasi perendaman), masing-masing perlakuan diulang sebanyak 3 kali sehingga diperoleh 27 percobaan. tanaman. Parameter yang diamati adalah tinggi tanaman, jumlah daun, berat segar, dan volume akar. Berdasarkan hasil penelitian dapat disimpulkan bahwa pemberian pupuk organik dari kotoran babi yang diinkubasi dengan perendaman dan tanpa perendaman tidak memberikan perbedaan yang nyata terhadap tinggi tanaman, jumlah daun, dan volume akar tetapi berbeda nyata terhadap berat segar tanaman. tanaman selada. Kata kunci: Pupuk organik, pupuk kandang, kotoran babi, inkubasi, tanaman selada.